Vivienda nómada: solución de vivienda móvil en Costa Rica para ambientes urbanos y rurales sostenibles - Solis-Mejia, Isaac Jose (2022)
Abstract This work references, synthesizes, specifies, and describes information, elements and interactions that generate quantitative and qualitative differences regarding the behavior of the individual and their home, framed in the context of the historical evolution of the human species and the different architectural concepts under sustainability criteria. It is through the understanding of the historical process of the human species in the development, effort and improvement of what traditional sedentary housing means that contributes and inspires the management of new research processes to define and propose a new model of contemporary mobile housing, based on the nomadic origin of our species. It is through professional experience, research, and citation of existing formal documentation, that a nomadic mobile housing solution is proposed that allows to alleviate contemporary urban and rural environments, to comply with the existing land use regulations of Costa Rica being different from the traditional sedentary model.